Identification and validation of candidate genes dysregulated in alveolar macrophages of acute respiratory distress syndrome - Mao, Yong; Lv, Xin; Xu, Wei; Ying, Youguo; Qin, Zonghe; Liao, Handi; Chen, Li; Liu, Ya (PeerJ, 2021)
Background Acute respiratory distress syndrome (ARDS) is a common cause of death in ICU patients and its underlying mechanism remains unclear, which leads to its high mortality rate. This study aimed to identify candidate genes potentially implicating in the pathogenesis of ARDS and provide novel therapeutic targets. Methods Using bioinformatics tools, we searched for differentially expressed genes (DEGs) in an ARDS microarray dataset downloaded from the Gene Expression Omnibus (GEO) database. Afterwards, functional enrichment analysis of GO, KEGG, GSEA and WGCNA were carried out to investigate the potential involvement of these DEGs. Moreover, the Protein–protein interaction (PPI) network was constructed and molecular complexes and hub genes were identified, followed by prognosis analysis of the hub genes. Further, we performed qRT-PCR, Western Blot and flow cytometry analysis to detect candidate genes of CCR2 and FPR3 in macrophage model of LPS-induced ARDS and primary alveolar macrophages(AMs). Macrophage chemotaxis was evaluated using Transwell assay. Results DEGs mainly involved in myeloid leukocyte activation, cell chemotaxis, adenylate cyclase-modulating G protein-coupled receptor signaling pathway and cytokine-cytokine receptor interaction. Basing on the constructed PPI network, we identified five molecular complexes and 10 hub genes potentially participating in the pathogenesis of ARDS. It was observed that candidate genes of CCR2 and FPR3 were significantly over-expressed in primary alveolar macrophages from ARDS patients and macrophgae model of LPS-induced ARDS. Moreover, in vitro transwell assay demonstrated that CCR2 and FPR3 down-regulation, respectively, inhibited LPS-triggered macrophage chemotaxis toward CCL2. Finally, a positive correlation between FPR3 and CCR2 expression was confirmed using pearson correlation analysis and Western Blot assay. Conclusions Our study identified CCR2 and FPR3 as the candidate genes which can promote macrophage chemotaxis through a possible interaction between FPR3 and CCL2/CCR2 axis and provided novel insights into ARDS pathogenesis.
Keywords: ARDS; Macrophage; FPR3; CCR2; Chemotaxis